PERLINDUNGAN HUKUM NARAPIDANA DARI TINDAK KEKERASAN ANTAR NARAPIDANA DI RUTAN CIPINANG - Laurensius; Subhan Zein Sgn (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Legal protection is all efforts to fulfill rights and provide assistance to provide a sense of security to criminals. Legal protection for criminals can be realized in various forms, namely through health services, legal aid, obtaining remission and so on. Legal protection is something that protects legal subjects through applicable laws and regulations and its implementation is enforced by means of a sanction. As a legal state, prisoners' rights are protected and recognized by law enforcement. In Article 12 of Law no. 22 of 2022 concerning Corrections states that prisoners must also have their rights protected even if they have violated the law. In addition, the government of the Republic of Indonesia strives to promote, protect, respect, realize and uphold the human rights of prisoners in detention centers.